DIAGNOSTIC ANALYSIS OF CATASTROPHIC FLOOD OVER EASTERN INDIA IN JULY 2017 - A CASE STUDY (MAUSAM, 2020)
Floods are very common in eastern India during southwest monsoon season. It brings a lot of misery to the people of this region. Every year eastern Indian states namely West Bengal, Odisha and Bihar witness such types of flood during monsoon period. Major river basins in eastern India are Ganga river basin in Bihar and West Bengal area, Odisha has three river basins namely Mahanadi, Subarnarekha, Brahmani and Baitarani        [Fig. 1(a)]. As majority of tributary rivers of Ganga passing through Bihar and West Bengal; these two states are more prone to massive flood during monsoon season. The abnormal occurrence of rainfall generally causes floods. It occurs when surface runoff exceeds the capacity of natural drainage. The heavy rainfall is frequently occurring event over the area during South-West Monsoon (SWM) every year. The geographical location of the area, orography and its interaction with the basic monsoon flow is considered as one of prime factors of these heavy rainfall activities. Synoptically, the latitudinal oscillation of eastern end of the Monsoon Trough and the synoptic disturbances formed or passing over the eastern India region and / or its neighbourhood that brings moisture laden Easterly or South-Easterly winds over the area are the main causes responsible for heavy rainfall in this area.